The Effectiveness of Reality Group Counseling with Confrontation and Being-Positive Techniques to Improve Students’ Self-Control (Jurnal Bimbingan Konseling, 2020)
Self-control is an ability to control impulsive behavior, stimulus, decision making process, and anticipate any phenomena. This study aimed to examine the effectiveness of reality group counseling with confrontation and being-positive techniques on the improvement of students’ self-control. It used pretest and multiple posttest design. Further, purposive sampling technique was employed to select 21 experimental subjects to be placed in three groups randomly so that each consisted of seven students. The students’ data were collected using self-control scale. Based on mixed ANOVA test, the reality group counseling with confrontation and being-positive techniques gained (F (1,18) = 8.255, p <0.01). Moreover, the researchers found an interaction effect between time and group on students’ self-control, namely (F (2.13, 19.19) = 8.156, p <0.05). Thus, this study reveals that the combination of confrontation and being-positive techniques results an interesting implication and is suggested to be applied in the service of reality group counseling.